Access Patterns of Online Materials in a Blended Course. (25th December 2012) - Asarta, Carlos J.; Schmidt, James R.
ABSTRACT: Patterns in student accesses of online materials and their effects upon student performance in a blended course are examined. Our blended course is an introductory business and economic statistics course where lectures are only available online while the traditional class period is used for complementary learning activities. Timing, volumes, intensity, and consistency of the student accesses of the online lectures are considered. Using bivariate and multivariate analyses, measures of timing and consistency are shown to be related to student performance but volumes and intensity of accesses are not.